Blue whale (Balaenoptera musculus) occurrence off the Galapagos Islands, 1978-1995 - M. Palacios, Daniel (J. Cetacean Res. Manage., 1999)
Twenty-three blue whale (Balaenoptera musculus) sightings made in the vicinity of the Galipagos Islands (~00°S, 90°W) between 1978-1995 are analysed. Blue whales occurred seasonally in the austral winter/spring months. A significant proportion of the sightings (13 co 56.5%) had a tendency to occur on the same day or on consecutive days in a given year. Five (21.7%) of the sightings were of groups of three or more individuals, Distribution was to the west and southwest of the Galipagos archipelago, where a plume of coo!, Uupwelling-enriched surface water with high planktonic biomass develops during this season. Blue whales were observed feeding on surface swarms of the euphuusiid Nyctiphanes simplex in 1993, Defecation was commonly seen, The external appearance of these whales suggests they were true blue whales (B.2. interniedia). Much of the evidence from this study suggests a Souther Hemisphere stock feeding west of the Gulipagos during the austral winter/spring months. Alternatively, they may' belong fo a presumed eastern tropical Pacific stack of blue whales which exploits the productive habitars of the Cost Rica Dome and the Peruvian/Ecuadorian coast.